Simulation temperature distribution of solar air heater / Nor Syafiqah Mohamed Kassim - Mohamed Kassim, Nor Syafiqah (2008)
A mathematical model for a single-pass, solar collector developed to determine the temperature distribution is presented. A flat-plate air collector design was considered. The collector divided into N sub cell of collector. The temperature of each sub cell of collector will be determined individually. By considering a steady state heat transfer using the thermal network analysis procedure, a set of heat balance equations are identified for the temperature distribution. There are three sets of each section. Because heat transfer coefficients were temperature dependent, a set of temperatures distribution was approximated which allowed the heat transfer coefficients to be evaluated as a first guess. Instead of solving the heat balance equations, a matrix inversion method was employed for each section using a standard sub-routine program. An iterative process was then used that enabled the calculated temperatures distribution for the collector closed to the guess value. The newly-calculated temperatures distributions were then compared with the initially-guessed temperatures. The iterative procedure was repeated until following temperature distribution values differed by greater than 0.1 °C. By this procedure, predictions of plate, glass and fluid temperatures for a collector of any length could be obtained. Although only single-pass type of flat-plate solar collector is considered here, the solution procedure could be extended to encompass most other collector designs.